'Ever in our Thoughts': Remembering Midland Men. (September 2014) - Batten, Sonia
<x content-type="archive" xml:space="preserve">Abstract</x> The contrasting, and sometimes conflicting, narratives of early twentieth-century remembrance are explored in this article. Individual personal inscriptions to Midlands men in the cemeteries of the Commonwealth War Graves Commission around the Ypres Salient are set against the prevailing motifs of remembrance as defined by Leicester's high-profile memorials to the South African War and the First World War. This comparison sets out to explore the extent to which public memorials directed and reflected the expressions of the next-of-kin, and discovers that the public narrative of remembrance was not as straightforward as it was sometimes presented.